2019
DOI: 10.21744/irjmis.v6n5.737
|View full text |Cite
|
Sign up to set email alerts
|

Development of district health system model policy implementation for improving health services

Abstract: National Health In implementing the autonomy function of decentralization, The Government of TTU District has rearranged the form and method of administering the district health or health development system which is organized in the District Regulation No. 09/2015. The objective of the study is to analyze how the development of a District Health System (DHS) model influences health services in the District of TTU, NTT. The research is Mix method approach. The results of quantitative: District Health System (DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The finding of H3 demonstrated that patient satisfaction has a positive effect on patient loyalty, with the highest results from the other hypotheses, point out that the influence of patient satisfaction must be a major concern for hospitals to increase the loyalty of patients. With regards to the final hypothesis, the finding demonstrated that patient satisfaction mediated the relationship between the quality of service and patient loyalty (Andaleeb, 2001;Aliman & Mohamad, 2016;Minggu et al, 2019).…”
Section: Conclusion and Recommendationmentioning
confidence: 98%
“…The finding of H3 demonstrated that patient satisfaction has a positive effect on patient loyalty, with the highest results from the other hypotheses, point out that the influence of patient satisfaction must be a major concern for hospitals to increase the loyalty of patients. With regards to the final hypothesis, the finding demonstrated that patient satisfaction mediated the relationship between the quality of service and patient loyalty (Andaleeb, 2001;Aliman & Mohamad, 2016;Minggu et al, 2019).…”
Section: Conclusion and Recommendationmentioning
confidence: 98%